Complete Genome Sequence Data of Novel Streptomyces angustmyceticus Strain CQUSa03, a Potential Biological Control Agent for Potato Oomycete and Fungal Diseases - Luo, Xiumei (Plant disease, 2023)
Streptomyces angustmyceticus CQUSa03 was recently isolated from the rhizosphere soil of a potato resistant variety, which showed strong biocontrol activity against potato late blight and other fungal diseases. To elucidate the biocontrol mechanism, the whole genome of CQUSa03 was sequenced using second-generation Illumina and third-generation Nanopore sequencing technologies. The assembled genome of CQUSa03 was 8,107,672 bp, containing one chromosome and three plasmids, with an average GC content of 72.29%, 6,914 protein-coding genes, 21 rRNA, and 68 tRNA. In addition, 29 important secondary metabolite biosynthetic gene clusters were identified in the CQUSa03 genome. The related genes of β-1,3-glucanase and chitinase, which can degrade the cell wall of fungal pathogens, were also found. CQUSa03 is predicted to have great potential in agriculture by producing a variety of antagonistic active compounds, cell wall hydrolases, and bacteriostatic peptides to control diseases. The genome sequence provided a theoretical basis for analyzing the biocontrol mechanism of S. angustmyceticus CQUSa03 and laid a foundation for the development and industrialization of biocontrol agents